ChemInform Abstract: Selective Thioacylation of Amines in Water: A Convenient Preparation of Secondary Thioamides and Thiazolines. Issue 24 (June 2015) - Pathak, Uma; Bhattacharyya, Shubhankar; Mathur, Sweta
Abstract: Primary thioamides (I) are used for the direct selective thioacetylation of primary amines (II) in water.